Military Sites from the Second World War in Lower Silesia as a Tourism Product: Current Use and Opportunities for Developmen - Chylińska, Dagmara (Turyzm/Tourism, 2006)
Lower Silesia has the potential to become a destination region for military tourism in Poland because of its significant collection of military sites from the Second World War. Some of them, like the 'Riese' underground complex, are already a tourism product with an existing tourist presence, developed tourist attractions, a tourism infrastructure, promotion and other complementary services. Other military sites - for instance the Middle Odra Fortified Line - could be a potential tourism product in connection with the 'Odra Trail’.